2004
DOI: 10.1111/j.1460-9568.2004.03222.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of variability in anatomical reconstruction techniques on models of synaptic integration by dendrites: a comparison of three internet archives

Abstract: The first step in building a realistic computational neuron model is to produce a passive electrical skeleton on to which active conductances can be grafted. For this, anatomically accurate morphological reconstructions of the desired cell type are required. In this study compartmental models were used to compare from a functional perspective three on-line archives of rat hippocampal CA1 pyramidal cell morphologies. The topological organization of cells was found to be similar for all archives, but several mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 37 publications
2
18
0
Order By: Relevance
“…In the present study, for a given cell morphology, fits to the 19 sets of experimental data yielded remarkably consistent parameter values indicating that the cells we sampled in our study were much more morphologically homogeneous than those we selected from the databases. Also, previous analyses of data from databases found that cells reconstructed in the same lab tend to have similar morphological parameters with much more heterogeneity found between labs (Ambros-Ingerson and Holmes, 2005;Scorcioni et al, 2004;Szilagy and De Schutter, 2004). Animal strain differences do not explain the wide differences in morphological characteristics shown in Table 4.…”
Section: Biologically Accurate Modelsmentioning
confidence: 56%
“…In the present study, for a given cell morphology, fits to the 19 sets of experimental data yielded remarkably consistent parameter values indicating that the cells we sampled in our study were much more morphologically homogeneous than those we selected from the databases. Also, previous analyses of data from databases found that cells reconstructed in the same lab tend to have similar morphological parameters with much more heterogeneity found between labs (Ambros-Ingerson and Holmes, 2005;Scorcioni et al, 2004;Szilagy and De Schutter, 2004). Animal strain differences do not explain the wide differences in morphological characteristics shown in Table 4.…”
Section: Biologically Accurate Modelsmentioning
confidence: 56%
“…While there are several other archives of rat hippocampal CA1 cells, they are heterogeneous in terms of animal strains and ages, reconstruction techniques, and morphometric properties (Scorcioni et al, 2004;Szilagyi and De Schutter, 2004). We have selected one of the largest homogenous archives of CA1 cells for this model, but we have also measured the number of bifurcations in CA1 dendritic trees from four other publicly available data sets.…”
Section: Methodsmentioning
confidence: 99%
“…To test the generalization of our results (Szilagyi and De Schutter 2004), we used a separate set of seven reconstructed young rat TTCs, which were provided to NeuroMorpho by A. Korngreen.…”
Section: Markrammentioning
confidence: 99%